PENINGKATAN HASIL BELAJAR TEMATIK MODE PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING SISWA KELAS II SD NEGERI 163086 TEBING TINGGI - Helmina Siagian (FIP Unimed, 2016)
This aim of this research is to improve learning result on thematic subject through contextual teaching and learning method. This classroom action research conducted by 2 cycles of the four phases: planning, implementation, observation, reflection. The subjects were students from class II, SDN 163086 Tebing Tinggi which amounted to 32 students. This study used a qualitative descriptive analysis technique. Based on data obtained from the measurement of the student learning outcomes on the cycle I of 78,12% and cycle II amounted to 87,5 % note there is an increase in student learning outcomes. This means learning the thematic using contextual teaching and learning method can improve learning outcomes in class II SDN 163086 Tebing Tinggi. Key word : CTL, learning result, thematic